Marketing Strategy of Fashion Course Program: Building Branding and Increasing Consumer Attraction at Fashion Institution Malang - Widiyawati, Irva; Prasetya, Luhur Adi; Ichwanto, Muhammad Aris (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
The study aims to find out the integrated marketing strategy in improving the institution's image, customer loyalty, and education program enrollment. The descriptive qualitative method used interviews with branch managers, sales coordinators, sales teams, and students of short and one-year course programs. Digital promotion through social media and attendance at local events successfully increased brand recognition by 35% on social media and 25% local event participation, building a professional and relevant image. Personalization strategies, such as schedule flexibility and quick response, increased student loyalty with a 30% increase in continuing education and a 45% satisfaction rate. The combination of value-based content on digital media and direct promotion through education fairs increased digital engagement by 50% and enrollment by 20%. Transparency of promotional information boosted prospective students' trust with 70% satisfaction, while quick response on digital platforms increased trust by 90% and clicks on promotional links by 35%. In conclusion, a holistic marketing strategy based on student needs and technology is the key to successfully strengthening the institution's image, increasing loyalty, and attracting new applicants. The results of this study offer strategic guidance for educational institutions facing increasing competition.